Microglia innate immune response contributes to the antiviral defense and blood–CSF barrier function in human choroid plexus organoids during HSV‐1 infection. Issue 2 (16th January 2023) - Qiao, Haowen; Chiu, Yuanpu; Liang, Xinyan; Xia, Shangzhou; Ayrapetyan, Mariam; Liu, Siqi; He, Cuiling; Song, Ruocen; Zeng, Jianxiong; Deng, Xiangxue; Yuan, Weiming; Zhao, Zhen
Abstract: The choroid plexus (ChP) is the source of cerebrospinal fluid (CSF). The ChP–CSF system not only provides the necessary cushion for the brain but also works as a sink for waste clearance. During sepsis, pathogens and host immune cells can weaken the ChP barrier and enter the brain, causing cerebral dysfunctions known as sepsis‐associated encephalophagy. Here, we used human ChP organoid (ChPO) to model herpes simplex virus type 1 (HSV‐1) infection and found ChP epithelial cells were highly susceptible to HSV‐1. Since the current ChPO model lacks a functional innate immune component, particularly microglia, we next developed a new microglia‐containing ChPO model, and found microglia could effectively limit HSV‐1 infection and protect epithelial barrier in ChPOs. Furthermore, we found the innate immune cyclic GMP‐AMP synthase (cGAS)–STING pathway and its downstream interferon response were essential, as cGAS inhibitor RU.512 or STING inhibitor H‐151 abolished microglia antiviral function and worsened ChP barrier in organoids. These results together indicated that cGAS–STING pathway coordinates antiviral response in ChP and contributes to treating sepsis or related neurological conditions.